SISTEM PENGENDALIAN INTERN ATAS PENGGAJIAN KARYAWAN PERUSAHAAN ( STUDI KASUS PT DAPO AGRO MAKMUR LUBUKLINGGAU) - Rudi Azhar (Jurnal Media Ekonomi (JURMEK), 2017)
This research examines the "internal control System Over Payroll employees at PT. Dapo Agro Prosperous Lubuklinggau" method used is descriptive qualitative. The object of research is the Payroll employees. The research is system of payroll employees i.e there are perangkapan tasks (duplicate tasks) between the creation of a list of employee salaries and sehinggga resulted in PT Agro Dapo Prosperous Lubuklinggau frequent lack of inflexible pieces and not on time as well as a delay in the procedure of making the payroll, this is because the keterlambtan in the procedure of making the creation of a list of employee salaries and inmi shows lack of internal control in accounting information system payroll accounting (SIA) PT. Dapo Agro Prosperous Lubuklinggau. in the system of payroll employees there is cheating in assessment percentage points (salary) for employees who got the work achievement, sehinggga result in a lack of supervision of each part and document his judgement is still way Manual.